Quantitative Transcriptomic and Proteomic Analysis of Fruit Development and Ripening in Watermelon (Citrullus lanatus) - Yu, Yongtao; Guo, Shaogui; Ren, Yi; Zhang, Jie; Li, Maoying; Tian, Shouwei; Wang, Jinfang; Sun, Honghe; Zuo, Yi; Chen, Yakun; Gong, Guoyi; Zhang, Haiying; et al. (Frontiers in Plant Science, 2022)
Fruit ripening is a highly complicated process, which is modulated by phytohormones, signal regulators and environmental factors playing in an intricate network that regulates ripening-related genes expression. Though Although transcriptomics is an effective tool to predicate predict protein levels, protein abundances are also extensively affected by post-transcriptional and post-translational regulations. Here, we used RNA sequencing (RNA-seq) and tandem mass tag (TMT)-based quantitative proteomics to study the comprehensive mRNA and protein expression changes during fruit development and ripening in watermelon, a nonclimacteric fruit. A total of 6,226 proteins were quantified, and the large number of quantitative proteins is the largest in proteomic studies of fruits to date, comparable to proteomic studies those in model organisms such as Oryza sativa L. and Arabidopsis. Base on our proteome methodology, Integrative integrative analysis of the transcriptome and proteome showed that the mRNA and protein levels were poorly correlated, and the correlation coefficients decreased during fruit ripening. Proteomic results showed that proteins involved in alternative splicing and ubiquitin-proteasome the ubiquitin proteasome pathway were dynamically expressed during ripening. Furthermore, the spliceosome and proteasome were significantly enriched by Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, suggesting that post-transcriptional and post-translational mechanisms might play important roles in regulation of fruit ripening-associated genes expression, which might account for the poor correlation between mRNAs and proteins during fruit ripening. Our comprehensive transcriptomic and proteomic data offer a valuable resource for watermelon research, and provide new insights into the molecular mechanisms underlying the complex regulatory networks of fruit ripening.